Offensive Screens: The Italy-China Diplomatic Agreement (1936–37) and the Transnational Censorship of Films. - Keating, Carla Mereu; Zhang, Xiaochun; O'Sullivan, Carol (Historical Journal of Film, Radio & Television, 2023)
Between late 1936 and early 1937 Italy and China became embroiled in a series of diplomatic exchanges about two controversial films. One was Abyssinia (dir. Kopalin, 1936), a Soviet documentary feature about Italy's invasion of Ethiopia, whose screening in a Shanghai cinema triggered a riot in February 1937. The other was The General Died at Dawn (dir. Milestone, 1936), a Paramount melodrama set in 1920s war-torn China whose international exhibition in late 1936, including in Italy, was criticised by the Chinese government. This article describes the reactions of diplomats and of local pressure groups to the exhibition of these films and to their 'offensive' representations of Italian colonialism and of China's internal politics and people. Research in classified diplomatic files shows the involvement of the Italian authorities in the organisation of a violent attack on the Isis cinema in Shanghai in February 1937, and provides rich detail about the inner workings of Fascist government officials in Rome and in Shanghai which could not be obtained from press reports alone. Both film cases foreground the limited power of intervention of national censorship boards and illustrate the types of actions and actors involved in transnational film exchanges where questions of national prestige or political authority are at stake. They also bear witness to a momentous time of geo-political transition and alliance-making in the lead-up to the Second World War.